PENGARUH EARNING PER SHARE, PROFITABILITAS, DAN KEBIJAKAN DIVIDEN TERHADAP HARGA SAHAM PADA PERUSAHAAN INDEKS LQ45 PERIODE 2018-2021 - Silvi Ayu Saputri; Firda Zulfa Fahriani (Reinforce: Journal of Sharia Management, 2023)
One of the factors which influence the movement of stock prices is the company's fundamentals. This company's fundamental analysis can use information from financial reports. One of the financial statement analysis techniques is to use financial ratios. The purposes of this study are to determine the effect of earnings per share, profitability, and dividend policy on stock prices in LQ45 index companies for the 2018-2021 period. This study uses a quantitative approach to the type of associative research. The sampling technique in this study used a purposive sampling method and obtained a sample of 11 companies in each period. The data used is secondary data obtained from the Indonesia Stock Exchange website, namely www.idx.co.id, which is in the form of data on company financial reports listed on the LQ45 Index for the 2018-2021 period. The data analysis method in this study used panel data regression analysis in testing the data in the research to be carried out using the Eviews 10 software program. The results of this study indicate that 1) Partial earnings per share has a positive and significant effect on stock prices, 2) Partial profitability has a positive and significant effect on stock prices, 3) Partial dividend policy has no significant effect on stock prices, 4) Simultaneously, earnings per share, profitability, and dividend policy have a significant effect on stock prices in LQ45 Index companies for the 2018-2021 period.